Paridhi - Mūrti, Sudhā (Lōkaśikṣaṇa Trasṭ Granthamāle, 2004)
Novel, based on social theme; previously published in Karmaveera, a Kannada magazine.
A novel - Kannada in kanares. Schr
Keywords: Kannada; Roman